Inside Mycobacterium bovis SB0120 spoligotype circulating in Italy: analysis of the most frequent genotypes by whole genome sequencing - Scaltriti, Erika; Iyad, Karaman; Boniotti, Maria Beatrice; Menozzi, Ilaria; Bolzoni, Luca; Ippolito, Dorotea; Ciarello, Flavia Pruiti; Loda, Daniela; D’Incau, Mario; Zanoni, Mariagrazia; Presti, Vincenzo Di Marco Lo; Mazzone, Piera; et al. (Frontiers in Microbiology, 2024)
Bovine tuberculosis (bTB) is a chronic inflammatory disease primarily caused by Mycobacterium bovis. The infection affects domestic animals and wildlife, posing a zoonotic risk to humans. To understand the dynamics of transmission and genetic diversity in Italy’s M. bovis population, we conducted whole-genome sequencing (WGS) analysis on two prevalent genotypes, belonging to Spoligotype SB0120, identified in different geographical and temporal contexts. By comparing these genomes with international M. bovis isolates, we identified a distinct clade within the lineage La1.2, encompassing the Italian SB0120 isolates, indicating a genomic segregation of Italian M. bovis from other European isolates. Within Italy, a significant level of genetic variability emerged across regions, while isolates within epidemiologically linked outbreaks exhibited minimal genetic diversity. Additionally, isolates derived from cattle and wild boars within a tuberculosis hotspot in Central Italy and from cattle and black pigs in Sicily formed unified clonal clusters. This indicates the presence of persistent strains circulating in the examined regions. The genetic diversity within herds was limited, as specific clones endured over time within certain herds. This research enhances our comprehension of the epidemiology and transmission patterns of bTB in Italy, thereby aiding the development of precise control strategies and disease management. Using WGS and implementing standardized protocols and databases will be pivotal in combating bTB and promoting One-Health approaches to address this noteworthy public health concern.